Peranan Lembaga Perlindungan Saksi dan Korban dalam Implementasi Restitusi terhadap Kasus Tindak Pidana Perdagangan Orang: Studi Putusan Pengadilan Negeri Bajawa Nomor 45/PID.SUS/2023 di Nusa Tenggara Timur - Astiana Diana Delima; Aksi Sinurat; Orpa Ganefo Manuain (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Human trafficking is a crime that causes physical, psychological, social, and economic harm to victims, thereby requiring effective legal protection. This study aims to analyze the role of the Witness and Victim Protection Agency (LPSK) in the implementation of restitution for victims of human trafficking in Decision Number 45/Pid.Sus/2023 of the Bajawa District Court and to examine the obstacles encountered in its implementation. This research employs an empirical juridical method with a socio-legal approach. Data were obtained through interviews and library research, then analyzed descriptively and qualitatively. The results indicate that LPSK has carried out its role through legal assistance, physical and psychological protection, psychosocial rehabilitation, and the submission of restitution claims for victims. However, the implementation of restitution has not been fully effective due to several obstacles, including weak coordination among law enforcement agencies, limited restitution execution mechanisms, limited institutional resources, and low victim awareness regarding restitution rights. Therefore, stronger coordination, supervision, and restitution enforcement mechanisms are needed to ensure effective victim protection and victim-oriented recovery in cases of human trafficking.